2013
DOI: 10.1002/prca.201300009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gamma irradiation and 15 days of subsequent ex vivo storage on the cytosolic red blood cell proteome analyzed by 2D‐DIGE and Orbitrap MS

Abstract: Gamma irradiation and subsequent ex vivo storage according to the Council of Europe guidelines were found to affect RBC protein structures. The validated marker proteins can serve as a basis for the development of a screening assay to monitor the quality of irradiated RBC concentrates during ex vivo storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Irradiation of blood is recommended to prevent TA-GVHD and to reduce the side effects of transfusions, transplants, and cancer therapies (Weinmann et al, 2000;Agarwal et al, 2005;Walpurgis et al, 2013;Santacruz-Gomez et al, 2014;Tabatabaei et al, 2016;Acosta-Elías et al, 2017). The blood can be irradiated before, during, and after storage, depending on the patient's necessities, but a common characteristic of irradiated blood is that RBCs are prone to hemolysis and, therefore, they are more fragile in circulation.…”
Section: Rbc Alterations By Ionizing Radiation and Characterization Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Irradiation of blood is recommended to prevent TA-GVHD and to reduce the side effects of transfusions, transplants, and cancer therapies (Weinmann et al, 2000;Agarwal et al, 2005;Walpurgis et al, 2013;Santacruz-Gomez et al, 2014;Tabatabaei et al, 2016;Acosta-Elías et al, 2017). The blood can be irradiated before, during, and after storage, depending on the patient's necessities, but a common characteristic of irradiated blood is that RBCs are prone to hemolysis and, therefore, they are more fragile in circulation.…”
Section: Rbc Alterations By Ionizing Radiation and Characterization Techniquesmentioning
confidence: 99%
“…Studies with AFM have shown dose-dependent damage on mice RBCs after gamma irradiation, with the appearance of nanopores, crater-like vesicles, and changes in membrane roughness (Walpurgis et al, 2013;AlZahrani and Al-Sewaidan, 2017;Taqi et al, 2019). Here, AFM renders invaluable information at nanoscale dominions on RBCs under irradiation stress.…”
Section: Rbc Alterations By Ionizing Radiation and Characterization Techniquesmentioning
confidence: 99%
“…The removal of T-lymphocytes helps prevent graft-versus-host reactions during transfusion. To study the long term effect of high dose IR, red blood cells (RBCs) were irradiated with 30 Gy, and proteins were differentially dye-labeled and then separated by 2D gel electrophoresis [ 74 ]. Protein spots that showed differences between irradiated and controls were identified by in-gel digestion followed by mass spectrometry (LC-MS/MS).…”
Section: Prior Studies Using Proteomic Analysis After Ir Exposurementioning
confidence: 99%